Murder for Lunch - Murphy, Haughton (MysteriousPress.com/Open Road, 2016)
Cover Page – Title Page – Dedication – 1 Graham Donovan – 2 George Bannard – 3 Reuben Frost – 4 Death at the Club – 5 Arrangements – 6 A Nasty Spill – 7 Emergency Sessions – 8 Requiescat in Pace – 9 Bad News and Another Luncheon – 10 Roger Singer – 11 Police – 12 Executive Committee Meeting – 13 A Simplification and a Complication – 14 Three Interviews – 15 Dinner Dance – 16 A Distraught Wife – 17 New Information – 18 Another Country – 19 Some Breaks – 20 An Evening at Home – 21 More Breaks – 22 Climax – 23 Cleanup – 24 Lunch Without Murder – Preview: Murder Takes a Partner – About the Author – Copyright Page.
Description based on publisher supplied metadata and other sources
Keywords: Detective and mystery stories; Electronic books